Desarrollo de una bebida mixta tipo néctar con cápsulas de Aloe vera (L.) Burm. f. y vitamina C (2019)
The market of natural products at a nutritional, medicinal and industrial level, has increased remarkably, promoting innovation and research and the use of vegetable and animal raw materials. The objective of this research was to design a nectar, with a combination of fruit and vegetable matrices such as grape, spinach, blackberry, blueberry, yacon, enriched with Aloe vera capsules and vitamin C. Three formulations were proposed varying the number of ingredients in the mixture; the most acceptable treatment was selected through sensory evaluation in an untrained panel. All the nectars had a good organoleptic acceptance, however, 50% of the panelists showed preferences for the treatment 1, it contained 13% of grape, 4% of spinach, 3% of blueberry and blackberry, 2% of yacon, the remaining percentage corresponded to the amount of water and sugar used in the formulation. To the treatment with greater acceptance (T1) the physical-chemical attributes were analyzed, showing a pH of 2.96; 12.11°Brix, color, smell and appearance normal and stable, likewise the presence of mesophilic bacteria, fungi and yeasts, E. coli and Salmonella was evaluated. In order to enrich the product, capsules of A. vera and vitamin C were prepared to be incorporated into the nectar. This type of product promotes the consumption of fruits and vegetables in processed foods of frequent use such as nectars.